IDENTIFIKASI DAN PENGUKURAN KETERAMPILAN PROSES SAINS PESERTA DIDIK KELAS XII SMA YPK SENTANI MELALUI PRAKTIKUM KIMIA - Dolfina Costansah Koirewoa; Irwandi Yogo Suaka (As-Sulthan Journal of Education, 2026)
This study aims to provide information and measure the science process skills of grade XII students at YPK Sentani High School in Jayapura Regency. This study applies a quantitative quasi-experimental research method. The type of experimental design used is a One Shot Case Study. Based on the type of data analysed, this research is a mixed-method study with data collection using observation inventory sheets and practical work documents carried out for 19 grade XII science students. The results of this study indicate that the indicators of science process skills (KPS) of grade XII students at YPK Sentani Senior High School measured in each practical topic include observation, using tools and/or materials, carrying out practical work, asking questions, making predictions, and communicating. Furthermore, the percentage of achievement of science process skills identified shows that in the acid-base titration practicum, the indicators were observation 26.32%, using tools and materials 78.95%, carrying out practicums 52.63%, asking questions 26.32%, interpreting data 47.37% and communicating 31.58%. Meanwhile, in the experiment on factors affecting reaction rate, observation was 100%, while more than 50% were able to use tools and materials and carry out the experiment, while most (>50%) were not yet able to master the indicators of asking questions, interpreting data, and communicating.